Does bullying cause emotional problems? A prospective study of young teenagers - Bond, Lyndal (BMJ, 2001)
OBJECTIVES: To establish the relation between recurrent peer victimisation and onset of self reported symptoms of anxiety or depression in the early teen years. DESIGN: Cohort study over two years. SETTING: Secondary schools in Victoria, Australia. PARTICIPANTS: 2680 students surveyed twice in year 8 (aged 13 years) and once in year 9. MAIN OUTCOME MEASURES: Self reported symptoms of anxiety or depression were assessed by using the computerised version of the revised clinical interview schedule. Incident cases were students scoring ⩾12 in year 9 but not previously. Prior victimisation was defined as having been bullied at either or both survey times in year 8. RESULTS: Prevalence of victimisation at the second survey point in year 8 was 51% (95% confidence interval 49% to 54%), and prevalence of self reported symptoms of anxiety or depression was 18% (16% to 20%). The incidence of self reported symptoms of anxiety or depression in year 9 (7%) was significantly associated with victimisation reported either once (odds ratio 1.94, 1.1 to 3.3) or twice (2.30, 1.2 to 4.3) in year 8. After adjustment for availability of social relations and for sociodemographic factors, recurrent victimisation remained predictive of self reported symptoms of anxiety or depression for girls (2.60, 1.2 to 5.5) but not for boys (1.36, 0.6 to 3.0). Newly reported victimisation in year 9 was not significantly associated with prior self report of symptoms of anxiety or depression (1.48, 0.4 to 6.0). CONCLUSION: A history of victimisation and poor social relationships predicts the onset of emotional problems in adolescents. Previous recurrent emotional problems are not significantly related to future victimisation. These findings have implications for how seriously the occurrence of victimisation is treated and for the focus of interventions aimed at addressing mental health issues in adolescents.